ANALISIS INOVASI, PROMOSI, DAN KOMPETENSI MARKETER TERHADAP KEPUTUSAN PEMBELIAN PRODUK BATIK ARCOBALENO DI SURAKARTA - Shady Adam Gultom; Sudarwati Sudarwati; Istiqomah Istiqomah (ITB AAS INDONESIA Surakarta, 2019)
This study aims to examine the effect of innovation, promotion, and marketer competence on the decision to purchase arcobaleno batik products in Surakarta. The population in this study were 200 consumers of arcobaleno batik, while the sample used was 100 consumers of batik products in the company Arcobaleno using quantitative methods, namely data measured in the form of numbers. The results of this study indicate that, marketer competencies significantly have an influence on purchasing decisions of batik products in arcobaleno companies, while innovation and promotion variables have no influence on purchasing decisions. Based on the test of the coefficient of determination (R2) it is known that the adjusted R square value is 0.222 or equal to 22.2%. This means that 22.2% of purchasing decisions can be explained by independent variables of innovation, promotion, and marketer competence. While the remaining 77.8% is explained by other variables besides the explanatory or independent variables outside of this study. Keyword : innovation, promotion, marketer competence, purchase decision